Predictors of mortality in children with lupus nephritis - Lukman Oktadianto; Risky Vitria Prasetyo; Ninik Asmaningsih Soemyarso; Mohammad Sjaifullah Noer (Paediatrica Indonesiana, 2014)
Background Renal involvement during the clinical course ofsystemic lupus erythematosus (SLE) is generally considered to bethe most important factor influencing disease prognosis in termsof morbidity and mortality. Various factors have been reported toinfluence the prognosis of lupus nephritis (LN).Objective To analyze clinical signs and laboratory parameters thatmight serve as predictors associated with mortality in pediatricLN.Methods Retrospectively, medical records of children with LNat Soetomo Hospital from 1998 to 2011 were studied. Diagnosisof SLE was based on Revised American Rheumatism Associationcritera, while patients with clinical manifestations of hypertension,abnormal urinalysis, and serum creatinin > 1 mg/dL wereconsidered as lupus nephritis. Cox proportional hazard modelingwas used to assess for associations of clinical signs and laboratoryparameters with mortality. Kaplan-Meier survival analysis wasused to assess the cumulative survival from the time of diagnosisto the outcome.Results There were 57 children with LN of whom 43 (75%) weregirls. The female-to-male ratio was 3:1. Subjects’ mean age was 10.6(SD 6.87) years. The mean time of observation was 51 (SD 74.54)months and 23 (40%) children died. Age, gender, hypertension,hematuria, proteinuria, and anemia were not significant aspredictors for mortality. However, hypertensive crisis (HR=2.79;95%CI 1.16 to 6.75; P=0.02) and initial glomerular filtration rate(GFR) of <75 mL/min/1.73m2 (HR=3.01; 95%CI 1.23 to 7.34;P=0.01) were significant predictors of mortality in children with LN.The mean survival time of LN with hypertensive crisis and initialGFR <75 mL/min/1.73m2 was 36.9 (SD 12.17) months.Conclusion Hypertensive crisis and GFR <75 mL/min/1.73m2 aresignificant predictors of mortality in children with LN.